2015
DOI: 10.1002/mma.3452
|View full text |Cite
|
Sign up to set email alerts
|

A posteriori error analysis for nonconforming approximation of multiple eigenvalues

Abstract: In this paper, we study an a posteriori error indicator introduced in E. Dari, R.G. Durán, and C. Padra, Appl. Numer. Math., 2012, for the approximation of the Laplace eigenvalue problem with Crouzeix–Raviart nonconforming finite elements. In particular, we show that the estimator is robust also in presence of eigenvalues of multiplicity greater than one. Some numerical examples confirm the theory and illustrate the convergence of an adaptive algorithm when dealing with multiple eigenvalues. Copyright © 2015 J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…is the solution of Problem (2.4) by the Morley element and λ M is the i-th eigenvalue, it follows from the theory of nonconforming eigenvalue approximations, see for instance, [2,3,5,16,40] and the references therein, that there exists u ∈ M(λ) with λ = λ i such that…”
Section: The Corresponding Canonical Interpolation Operator πmentioning
confidence: 99%
“…is the solution of Problem (2.4) by the Morley element and λ M is the i-th eigenvalue, it follows from the theory of nonconforming eigenvalue approximations, see for instance, [2,3,5,16,40] and the references therein, that there exists u ∈ M(λ) with λ = λ i such that…”
Section: The Corresponding Canonical Interpolation Operator πmentioning
confidence: 99%
“…To capture the singularities, a popular way is to use adaptive scheme. Several studies have shown that an effective adaptive strategy for multiple eigenvalues should consider all involved discrete eigenfunctions [3,9,17], otherwise the singularities of the target eigenfunctions may be resolved in a wrong way. However, the main issue is that in general it is not known a priori the multiplicity of an eigenvalue of the continuous problem, which in turn brings difficulties to the design of efficient adaptive methods.…”
Section: Square Ringmentioning
confidence: 99%
“…This result, however, does not directly apply to nonconforming finite element methods. A generalisation for the Crouzeix-Raviart FEM for the eigenvalues of the Laplacian is given in (Boffi et al, 2014) where it is used that the nonconforming finite element space has an H 1 -conforming subspace. The Morley finite element does not satisfy a corresponding condition; this paper develops a new technique which allows the proof of eigenvalue error estimates of the form |λ j − λ ℓ,j | max{λ j , λ ℓ,j } ≤ C sin 2 a,NC (W, W ℓ ).…”
Section: Introductionmentioning
confidence: 99%